PEMBERDAYAAN MASYARAKAT PESISIR MELALUI PENGOLAHAN IKAN DENGAN MENGGUNAKAN KOMPOR BERBAHAN BAKAR OLI BEKAS - Amir Hidayat; Maulita Maulita; Fabiola Luturmas; Indrawati Indrawati (Politeknik Negeri Sriwijaya, 2023)
People who have a fish processing business into snacks in the form of amplang in Sanga Sanga Dalam Village, Kutai Kartanegara Regency, also feel the impact of the scarcity of fuel sources for cooking, namely LPG. There is a need for alternative fuels that can be used to expedite the amplang business. Used oil-fueled stoves are an alternative that can be used to cook processed fish into amplang. This community empowerment activity aims to provide information and the use of alternative energy by using a used oil-fueled stove that can be used to cook processed fish into amplang. The introduction and operation of this used oil-fueled stove is needed to be able to facilitate the amplang business activities carried out by the community on the Mahakam river coast in Sanga Sanga Dalam village, Kutai Kartanegara. With this used oil-fueled stove it is hoped that it can facilitate business and can anticipate the scarcity of LPG, so that amplang production can run smoothly.